Energy consumption characteristics of concrete using granulated blast-furnace slag sand related to nucleation and propagation of microcracks. (10th September 2019) - Onoue, Kozo
Highlights: The use of BFS increases the static modulus of elasticity of concrete. The use of BFS decreases total strain energy and consumed energies inside concrete. Amount of damage in concrete under compressive stress is reduced by using BFS. Abstract: Recently, highly durable precast concrete using granulated blast-furnace slag sand (BFS) has been actively studied in Japan. Since BFS has a latent hydraulicity under alkaline conditions, it will improve the long-term strength and durability of concrete. In this study, to investigate the mechanisms of durability improvement of concrete with BFS, the energy consumption characteristics related to nucleation and propagation of microcracks in concrete specimens subjected to cyclic compressive loading are experimentally investigated. BFS concrete specimens with water-to-cement ratios of 0.35 and 0.50 are prepared and tested at material ages of 28 and 91 days. Normal concrete specimens using river sand are also prepared for comparison. Several types of energies are calculated from the areas under the stress–strain curves. The results show that, for the same water-to-cement ratio and the upper-limit stress ratio, the energy required to form microcracks at the initial loading, as well as the consumed energy in the constant region, are smaller for BFS concrete than for normal concrete. Thus, it is concluded that the damage done to BFS concrete during initial loading, as well as in the constant region during a fatigue process, is less than that done to normal concrete.